Randomised trial of mitral valve repair with leaflet resection versus leaflet preservation on functional mitral stenosis (The CAMRA CardioLink-2 Trial). Issue 5 (30th May 2017) - Chan, Vincent; Chu, Michael W A; Leong-Poi, Howard; Latter, David A; Hall, Judith; Thorpe, Kevin E; de Varennes, Benoit E; Quan, Adrian; Tsang, Wendy; Dhingra, Natasha; Yared, Kibar; Teoh, Hwee; et al.
Abstract : Background: The gold-standard treatment of severe mitral regurgitation (MR) due to degenerative disease is valve repair, which is surgically performed with either a leaflet resection or leaflet preservation approach. Recent data suggest that functional mitral stenosis (MS) may occur following valve repair using a leaflet resection strategy, which adversely affects patient prognosis. A randomised comparison of these two approaches to mitral repair on functional MS has not been conducted. Methods and analysis: This is a prospective, multicentre randomised controlled trial designed to test the hypothesis that leaflet preservation leads to better preservation of mitral valve geometry, and therefore, will be superior to leaflet resection for the primary outcome of functional MS as assessed by 12-month mean mitral valve gradient at peak exercise. Eighty-eight patients with posterior leaflet prolapse will be randomised intraoperatively once deemed by the operating surgeon to feasibly undergo mitral repair using either a leaflet resection or leaflet preservation approach. Secondary end points include comparison of repair strategies with regard to mitral valve orifice area, leaflet coaptation height, 6 min walk test and a composite major adverse event end point consisting of recurrent MR ≥2+, death or hospital readmission for congestive heart failure within 12 months of surgery. Ethics and dissemination: Institutional ethics approval has been obtained from all enrolling sites. Overall, there remains clinical equipoise regarding the mitral valve repair strategy that is associated with the least likelihood of functional MS. This trial hopes to introduce high-quality evidence to help surgical decision making in this context. Trial registration number: NCT02552771.